Andrea Szilasi - Dagenais, Francine (CV Photo, 1998)
Summary Andrea Szilasi finds her inspiration in science magazines and anatomy books. But however fascinated she may be with the inner workings of the human body, how it is quantified or depicted, hers is not a documentary interpretation of the corporeal. Rather, she casts her gaze upon the fragility of the body and ultimately upon the human condition. Szilasi confers a barren, ascetic quality to her images - just as she strips the space of cultural clues or context, she strips the central figure as well. When she focuses on human sexuality, for instance, she creates non-culturally specific, decontextualized hybrids. Like other artists working in the past decade, she relies on several destabilizing devices and distancing effects such as blurring the image, inverting the figure, weaving two photographs together; these elements combine to produce a cinematic impression. Francine Dagenais